Pengaruh Influencer Marketing Authenticity dan Trustworthiness terhadap Brand Attitude yang Dimoderasi oleh Perceived Value di Kota Surakarta - Ramadani, Risqi; Praswati, Aflit Nuryulia (STIE Indonesia Banking School, 2025)
The research explores the influence of influencer marketing authenticity and trustworthiness on brand attitude, moderated by perceived value among social media users in Surakarta. Data from 180 respondents aged 17 to 35 were collected through a questionnaire. The findings indicate that authenticity significantly enhances brand attitude, while trustworthiness does not have a significant effect. Additionally, perceived value strengthens the relationship between authenticity and brand attitude. The results highlight the importance of authenticity in influencer marketing strategies. Hypothesis testing results show that influencer marketing authenticity has a significant effect on brand attitude (p<0.05), while trustworthiness does not show a significant effect (p>0.05). Furthermore, perceived value reinforces the relationship between authenticity and brand attitude. These findings emphasize the importance of authenticity in influencer marketing strategies.